2018
DOI: 10.1158/1535-7163.mct-17-0605
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin mRNA Silencing and MEK Inhibition Display Synergistic Efficacy in Preclinical Tumor Models

Abstract: Colorectal carcinomas (CRC) harbor well-defined genetic abnormalities including aberrant activation of Wnt/β-catenin and MAPK pathways, often simultaneously. While the MAPK pathway can be targeted using potent small molecule drugs, including BRAF and MEK inhibitors, β-catenin inhibition has been historically challenging. RNA interference (RNAi) approaches have advanced to the stage of clinical viability, and are especially well-suited for transcriptional modulators such as β-catenin. In this study, we report t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
1
11
1
Order By: Relevance
“…Cadherin-associated protein beta 1 (β-catenin) is another known transcription factor that regulates the expression of MITF 43 . Previous studies have found that β-catenin contributes to the formation of BRAFi resistance in melanoma, which, however, is independent on its downstream canonical Wnt-signaling pathway 44,45 . Given that β-catenin could facilitate the proliferation and metastasis of melanoma in an MITF-dependent manner, MITF probably mediates the effect of β-catenin on BRAFi therapy in melanoma patients.…”
Section: Discussionmentioning
confidence: 95%
“…Cadherin-associated protein beta 1 (β-catenin) is another known transcription factor that regulates the expression of MITF 43 . Previous studies have found that β-catenin contributes to the formation of BRAFi resistance in melanoma, which, however, is independent on its downstream canonical Wnt-signaling pathway 44,45 . Given that β-catenin could facilitate the proliferation and metastasis of melanoma in an MITF-dependent manner, MITF probably mediates the effect of β-catenin on BRAFi therapy in melanoma patients.…”
Section: Discussionmentioning
confidence: 95%
“…Resistance to 5‐FU in CRC is a major clinical problem. While there are a number of mechanisms reported to be responsible for drug resistance, activation of several tissue polarity regulation pathways is quite appealing . Like wnt, notch, and hedgehog signaling pathways, YAP1 is an important regulator for embryonic development, organ size, cell differentiation, and cancer development .…”
Section: Introductionmentioning
confidence: 99%
“…We recommend the authors to assess the effects of procaine on glycogen synthase kinase-3β expression and/or β-catenin phosphorylation or nuclear translocation, with or without the δ-TT. An established Wnt/β-catenin inhibitor (reviewed in [17]) or gene silencing [18] would be more conclusive approaches in determining the role of Wnt/β-catenin in mediating the δ-TT on MC3T3 cells.…”
mentioning
confidence: 99%